2016
DOI: 10.3847/0004-637x/820/2/122
|View full text |Cite
|
Sign up to set email alerts
|

Radio Emission From Red-Giant Hot Jupiters

Abstract: When planet-hosting stars evolve off the main sequence and go through the red-giant branch, the stars become orders of magnitudes more luminous and, at the same time, lose mass at much higher rates than their mainsequence counterparts. Accordingly, if planetary companions exist around these stars at orbital distances of a few au, they will be heated up to the level of canonical hot Jupiters and also be subjected to a dense stellar wind. Given that magnetized planets interacting with stellar winds emit radio wa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(12 citation statements)
references
References 90 publications
(148 reference statements)
0
12
0
Order By: Relevance
“…References. (1) Farrell et al (2003); (2) Ryabov et al (2004); (3) Lazio et al (2004); (4) Shiratori et al (2006); (5) Lazio & Farrell (2007); (6) Stroe et al (2012); (7) Hallinan et al (2013); (8) Lynch et al (2018); (9) this article, Section 5.1.rell et al 2004;Lazio et al 2004;Stevens 2005; Grießmeier et al 2007a,b;Jardine & Collier Cameron 2008;Vidotto et al 2010b;Hess & Zarka 2011;Nichols 2011Nichols , 2012Vidotto et al 2012;See et al 2015;Vidotto et al 2015;Nichols & Milan 2016;Fujii et al 2016;Weber et al 2017a Weber et al ,b, 2018Lynch et al 2018;Wang & Loeb 2019;Kavanagh et al 2019;Shiohira et al 2020).One of the goals of these theoretical studies is to predict the radio flux and frequency of emission as observed from Earth. However, these predictions are hardly more than educated guesses, with associated uncertainties estimated as one order of magnitude for the flux density and a factor of 2-3 for Article number, page 2 of 29 J.D.…”
mentioning
confidence: 99%
“…References. (1) Farrell et al (2003); (2) Ryabov et al (2004); (3) Lazio et al (2004); (4) Shiratori et al (2006); (5) Lazio & Farrell (2007); (6) Stroe et al (2012); (7) Hallinan et al (2013); (8) Lynch et al (2018); (9) this article, Section 5.1.rell et al 2004;Lazio et al 2004;Stevens 2005; Grießmeier et al 2007a,b;Jardine & Collier Cameron 2008;Vidotto et al 2010b;Hess & Zarka 2011;Nichols 2011Nichols , 2012Vidotto et al 2012;See et al 2015;Vidotto et al 2015;Nichols & Milan 2016;Fujii et al 2016;Weber et al 2017a Weber et al ,b, 2018Lynch et al 2018;Wang & Loeb 2019;Kavanagh et al 2019;Shiohira et al 2020).One of the goals of these theoretical studies is to predict the radio flux and frequency of emission as observed from Earth. However, these predictions are hardly more than educated guesses, with associated uncertainties estimated as one order of magnitude for the flux density and a factor of 2-3 for Article number, page 2 of 29 J.D.…”
mentioning
confidence: 99%
“…Using scaling relations based empirically on the Solar System planets, several authors have determined that the exoplanets most likely to be detected by current radio telescopes are rare, and orbiting in extreme environments. These systems include hot Jupiters orbiting still-forming stars (Lazio et al 2004;Stevens 2005;Grießmeier et al 2005;Vidotto et al 2010), Jupiter-like planets orbiting giant-type stars (Fujii et al 2016), and orbiting stars that produce copious amounts of X-ray and UV emission (Nichols 2011(Nichols , 2012.…”
Section: Exoplanets and Other Polarised Transientsmentioning
confidence: 99%
“…Finally, Fujii et al [2016] have revisited the case of planets in orbit around evolved stars. Such stars have much higher mass loss rates than their main-sequence counterparts.…”
Section: On Exotic Targetsmentioning
confidence: 99%
“…However, previous work [Ignace et al, 2010] indicated that the stellar wind was not sufficiently ionized to lead to a strong radio emission from the planet. Fujii et al [2016] consider that the stellar wind could be ionized by UV and X-ray photons created by the accretion of the dense stellar wind onto the planet. In that case, the winds could indeed lead to strong magnetospheric radio emission from such planets, generating a potentially detectable radio signal.…”
Section: On Exotic Targetsmentioning
confidence: 99%